CO2 photoconversion to fuels under high pressure: effect of TiO2 phase and of unconventional reaction conditions. Issue 9 (17th September 2015) - Rossetti, I.; Villa, A.; Compagnoni, M.; Prati, L.; Ramis, G.; Pirola, C.; Bianchi, C. L.; Wang, W.; Wang, D.
<x xml:space="preserve">Abstract</x> Effect of CO2 saturation and reactor pressure on H2 (full triangles) and CH4 (circles) productivity at pH = 11.4, T = 65 °C. H2 productivity (empty triangles) at pH 5.5, T = 65 °C. Sample 0.1 wt% Au/P25.